Neuroimmunomodulation in Major Depressive Disorder: Focus on Caspase 1, Inducible Nitric Oxide Synthase, and Interferon-Gamma (2019)
Major depressive disorder (MDD) is one of the leading causes of disability worldwide, and its incidence is expected to increase. Despite tremendous efforts to understand its underlying biological mechanisms, MDD pathophysiology remains elusive and pharmacotherapy outcomes are still far from ideal. Low-grade chronic inflammation seems to play a key role in mediating the interface between psychological stress, depressive symptomatology, altered intestinal microbiology, and MDD onset. We review the available pre-clinical and clinical evidence of an involvement of pro-inflammatory pathways in the pathogenesis, treatment, and remission of MDD. We focus on caspase 1, inducible nitric oxide synthase, and interferon gamma, three inflammatory systems dysregulated in MDD. Treatment strategies aiming at targeting such pathways alone or in combination with classical therapies could prove valuable in MDD. Further studies are needed to assess the safety and efficacy of immune modulation in MDD and other psychiatric disorders with neuroinflammatory components. © 2018, The Author(s).